2004
DOI: 10.1021/bi048505f
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Fatty Acid Binding Protein:  Specificity and Functional Control as Revealed by Crystallographic Structure,

Abstract: Schistosoma mansoni fatty acid binding protein (Sm14) was crystallized with bound oleic acid (OLA) and arachidonic acid (ACD), and their structures were solved at 1.85 and 2.4 A resolution, respectively. Sm14 is a vaccine target for schistosomiasis, the second most prevalent parasitic disease in humans. The parasite is unable to synthesize fatty acids depending on the host for these nutrients. Moreover, arachidonic acid (ACD) is required to synthesize prostaglandins employed by schistosomes to evade the host's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The relatively short distance between water A1000 and O2 atom of caprylic and capric acid (2.46 and 2.48 Å , respectively) are not typical for hydrogen bonds length and might be result of partial saturation of binding site with ligand. On the other hand shorter than standard 2.7-3.0 Å length hydrogen bonds have been found in Relibase (Hendlich et al, 2003), in some crystal structures of other proteins with fatty acids as for example structures with PDBID: 2BAB (Liavonchanka et al, 2006), 2AG9 (Wright et al, 2005), 1VYG (Angelucci et al, 2004) and 3FYS (Nan et al, 2009). Reported distances were in the range 2.30-2.60 Å .…”
Section: Discussionmentioning
confidence: 91%
“…The relatively short distance between water A1000 and O2 atom of caprylic and capric acid (2.46 and 2.48 Å , respectively) are not typical for hydrogen bonds length and might be result of partial saturation of binding site with ligand. On the other hand shorter than standard 2.7-3.0 Å length hydrogen bonds have been found in Relibase (Hendlich et al, 2003), in some crystal structures of other proteins with fatty acids as for example structures with PDBID: 2BAB (Liavonchanka et al, 2006), 2AG9 (Wright et al, 2005), 1VYG (Angelucci et al, 2004) and 3FYS (Nan et al, 2009). Reported distances were in the range 2.30-2.60 Å .…”
Section: Discussionmentioning
confidence: 91%
“…Another pair grouped into class A was that of arachidonic acid (ACD) binding to both the β -barrel fatty acid binding protein Sm14 25 (PDB 1vyg) and to the α -orthogonal bundle prostaglandin H1 synthase 26 (PDB 1diy). The ligand carboxylate hydrogen-bonds to arginine, threonine, and tyrosine residues in one complex, and to arginine and tyrosine in the other (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these differences suggested that TsFABP1 and EgFABP1 may fulfill different functions, even when they share the residues that are involved in the ligand stabilization, characteristic of the iLBP subfamily iv. In the case of S. mansoni Sm14 the proteins shows a clear preference toward longer FAs [16]. An intriguing finding was that TsFABP1 showed a high affinity toward arachidonic acid.…”
Section: Groupmentioning
confidence: 98%
“…Most FABPs are members of the subfamily iv, characterized by the binding of a single ligand in an U-shaped conformation; other FABPs that are capable of binding one or two different FAs with a different bending, or even retinoid ligands, are included in subfamilies i, ii and iii [10]. The expression of two FABP isoforms have been reported for the trematodes Fasciola hepatica [11] and Fasciola gigantica [12], as well as for the cestodes Echinococcus granulosus [13], Mesocestoides vogae [9] and Taenia pisiformis [14], whereas only one was found in several schistosome species [15][16][17] and Clonorchis sinensis [18]. FABPs are involved in the storage and transport of lipids in E. granulosus [19].…”
Section: Introductionmentioning
confidence: 99%